A Critical Evaluation of E-Journals in Lis: A Case Study of Three Websites - Panda, K. C.; Kanungo, Arunima (Journal of Information and Knowledge, 2006)
Provides an insight in to the concept of e-journals and their growth. Vividly explains the taxonomy of e-journals along with the methodology employed in the study. Analyses and interprets data, pertaining to a total sample of 110 e-journals available in three websites using only three popular search engines (Google, Altavista, Yahoo), in regard to their subject coverage, country of publication, language of publication, year of publication, frequency and cost. Reveals that, 48.18% of the total e-journals in LIS cover IT as their thrust area; 63.37% of them are published from USA; 97.21% e-journals are published in English; 44.95% are published quarterly; and 67.42 % of them are fee-based journals. Interestingly, the publication of e-journals in LIS witnessed an unexpected decline in the three websites from 11 in 1995 to only 1 in 2003, the study asserts.